2007
DOI: 10.2224/sbp.2007.35.6.789
|View full text |Cite
|
Sign up to set email alerts
|

The Exposure of Primary School Teachers to Bullying: An Analysis of Various Variables

Abstract: The aim of this study was to analyze the variables involved in the bullying experiences of primary school teachers who attended in-service courses at the Aksaray and Esenköy training centers in Turkey. There were 315 participants in the study. A Turkish adaptation of the Negative Acts Questionnaire Scale (NAQ) developed by Einarsen and Raknes (1997) was used. Cronbach's alpha = .97, factor loads were determined to be between .42 and .82. Frequency, percentage, arithmetic mean, chi-square and variance analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 24 publications
4
16
0
12
Order By: Relevance
“…An examination of findings related to this sub-problem indicates that tendency to ignore their ideas and opinions, keeping information that would affect their performance from them, and being humiliated by being assigned to works beneath their competence are negative behaviors that teachers face more frequently than others. The findings of this study are parallel to those of studies conducted by Cemaloğlu, (2007b), Cemaloğlu and Kılınç (2012), Dick and Wagner (2001), Ertürk (2011), andSağlam (2008). Mobbing behaviors witnessed in educational institutions are generally directed to teachers' careers and mobbing behaviors that could harm personality and ego have a lower incidence rate, which is consistent with ethical expectations related to educational organizations because they regard ethics from the standpoint of education professionals as an ethical responsibility that they should fulfill in both their professional life at school and personal life (Furman, 2004;cited from Uğurlu, 2012).…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An examination of findings related to this sub-problem indicates that tendency to ignore their ideas and opinions, keeping information that would affect their performance from them, and being humiliated by being assigned to works beneath their competence are negative behaviors that teachers face more frequently than others. The findings of this study are parallel to those of studies conducted by Cemaloğlu, (2007b), Cemaloğlu and Kılınç (2012), Dick and Wagner (2001), Ertürk (2011), andSağlam (2008). Mobbing behaviors witnessed in educational institutions are generally directed to teachers' careers and mobbing behaviors that could harm personality and ego have a lower incidence rate, which is consistent with ethical expectations related to educational organizations because they regard ethics from the standpoint of education professionals as an ethical responsibility that they should fulfill in both their professional life at school and personal life (Furman, 2004;cited from Uğurlu, 2012).…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…Research conducted in educational organizations indicated that an overwhelming majority of teachers were exposed to at least one type of mobbing behavior and that 99.6 % of them were exposed to mobbing behaviors during their career (Aksu and Balcı, 2009;Blase and Blase, 2002;Cemaloğlu, 2007a;Cemaloğlu, 2007b;Hubert and Veldhoven, 2001;Riley, Duncan and Edwards, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This may be interpreted in several ways. One explanation would be that teachers witnessed harassment among pupils or other staff (23). Another would be that larger group of teachers witnessed harassment that happened to one person or a narrow group.…”
Section: Discussionmentioning
confidence: 99%
“…Factor analysis indicated one factor for 21 items, and total variance was 0.71, internal consistency co-efficient was 0.94 and factor loads were between 0.59 and 0.87. Cemaloglu (41)(42)(43) reports that scale items are loaded on one factor in other studies. In the present study, internal consistency coefficient was 0.90.…”
Section: Measures Negative Acts Questionnaire (Naq)mentioning
confidence: 97%